Consumer reaction to information on the labels of genetically modified food - Sebastian-Ponce, Miren Itxaso; Sanz-Valero, Javier; Wanden-Berghe, Carmina (Revista de Saúde Pública, 2014)
OBJECTIVE : To analyze consumer opinion on genetically modified foods and the information included on the label. METHODS : A systematic review of the scientific literature on genetically modified food labeling was conducted consulting bibliographic databases (Medline – via PubMed –, EMBASE, ISI-Web of knowledge, Cochrane Library Plus, FSTA, LILACS, CINAHL and AGRICOLA) using the descriptors “organisms, genetically modified” and “food labeling”. The search covered the first available date, up to June 2012, selecting relevant articles written in English, Portuguese or Spanish. RESULTS : Forty articles were selected after applying the inclusion and exclusion criteria. All of them should have conducted a population-based intervention focused on consumer awareness of genetically modified foods and their need or not, to include this on the label. The consumers expressed a preference for non-genetically modified products, and added that they were prepared to pay more for this but, ultimately, the product bought was that with the best price, in a market which welcomes new technologies. In 18 of the articles, the population was in favor of obligatory labelling, and in six, in favor of this being voluntary; seven studies showed the consumer knew little about genetically modified food, and in three, the population underestimated the quantity they consumed. Price was an influencing factor in all cases. CONCLUSIONS : Label should be homogeneous and clarify the degree of tolerance of genetically modified products in humans, in comparison with those non-genetically modified. Label should also present the content or not of genetically modified products and how these commodities are produced and should be accompanied by the certifying entity and contact information. Consumers express their preference for non-genetically modifiedproducts and they even notice that they are willing to pay more for it, but eventually they buy the item with the best price, in a market that welcomes new technologies.